PENGEMBANGAN PAKET PELATIHAN MENULIS EKSPRESIF SEBAGAI MEDIA KATARSIS KECEMASAN SISWA INTROVERT DI SMA - Ilmiyana Hikmah (Jurnal Konseling Pendidikan Islam, 2020)
Abstract : The purpose of this study was to develop a training package expressive writing as catharsis media introverted high school student anxiety. The research model used adapts from Borg and Gall. The product has been through expert test of BK, media, language and test of product user candidate and operational test. Data were collected using an anxiety scale questionnaire, introverted questionnaires, interviews and documentation studies. Data analysis techniques use descriptive statistics. The distribution of anxiety scale questionnaires and introverted scale is done in SMA 1 Pasuruan, distributed to 70 students in grade 10. From the division of questionnaires proved some students have high levels of anxiety and tend to introvert. Results of the assessment expert testing and test prospective users stating the product has met the eligibility criteria, accuracy, usefulness, the attractiveness and convenience. The results of product operational tests show that there are differences in anxiety levels of students before and after being treated using expressive writing training packages. For the introverted scale there are differences in introverted levels of students before and after being treated. Keywords : Training Packages, Expressive Writing, Catharsis, Anxiety, Introverts.